PENGUJIAN KRITERIA KAWASAN TERTENTU TERHADAP KOMPLEKS OBSERVATORIUM BOSSCHA SEBAGAI DASAR PENENTUAN BENTUK PENGELOLAAN KAWASAN - KATRINI D, NIKEN; BURHANUDIN, HANI (Jurnal Perencanaan Wilayah dan Kota, 2010)
Bosscha Observatory is one of a national asset and capital base astronomy research and education development in Indonesia and international cooperation in the field of astronomy. The existence of building construction within a radius of 2.5 km from Bosscha will heighten the intensity of the light that would reduce the quality of the astronomical telescope observations at Bosscha. Besides the threat of dust mixed roar of visitor activity and fine dust particles flying into space by the height of the recreational activity or while driving a car, it will also affect and degrade the quality of the observation telescope Bosscha. As one of the efforts to preserve, protect, and preserve the existence Bosscha, it should serve as Bosscha particular region. It is important to know beforehand whether Bosscha and the surrounding region is included in a particular region or not. Then the determination of certain types of areas are most appropriate for Bosscha, and how proper management efforts to Bosscha and the surrounding area.To determine whether Bosscha included in a particular region, then the testing criteria a particular region of the Bosscha Observatory Complex and the surrounding region with the assessment by experts, the weighting of each criterion and the classification of certain classes using classification Sturgest. In this study, the desired class is divided into two classes: suitable and unsuitable. Having obtained the results, we then re-tested every type of criteria specified by the same method to determine the type of a particular region is the most appropriate for Bosscha.Based on the analysis, it could be concluded that the Bosscha Observatory Complex and the surrounding region is included in a particular region and a particular type of area most appropriate for a specific region critical Bosscha is the result of the impact of human activity.